Technical-Environmental Assessment of Energy Management Systems in Smart Ports - Hoang Phuong Nguyen; Nguyen Dang Khoa Pham; Viet Duc Bui (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Shipping is facing huge pressure problems in this 21st century such as climate change and environmental pollution and the depletion of energy resources. Seaports are an important component of the shipping industry architecture. Although there is no common solution, seaports around the globe face the same challenge. Challenges raised include difficulties in integrating new technology into automation, traffic congestion, harmonizing residential communities around the port, quantifying and reducing CO2 emissions as well as planning for the energy transition. In addition, improving the adaptability of the port infrastructure in the context of increased pressure from market demand, labor shortage, and escalating prices should be considered. In that context, a smart port was born as a necessity. However, the understanding of smart ports is very limited. This review examines the recently published smart port literature to clarify the common concepts of smart ports and their development progress on the way to building a sustainable seaport ecosystem. Although smart port metrics and key port performance metrics are organized around four key performance areas including operations, environment, energy, and safety. However, a comprehensive review of all four key areas is very broad and difficult to cover in a review article. Therefore, this work focuses on analyzing and discussing the approaches and applications of the technology in smart port energy management systems. Our research has shown that different smart port founding perspectives play a decisive role in technology approaches to building a port energy management system including optimizing algorithms for energy consumption, balancing demand and energy production, and comprehensively integrating renewable energy. New findings in this study contribute to the elucidation of smart port concepts based on improving energy use and management efficiency with innovative technologies in the context of sustainable development of the shipping industry.